2013
DOI: 10.1210/jc.2012-3208
|View full text |Cite
|
Sign up to set email alerts
|

Excess Early Postnatal Weight Gain Leads to Thicker and Stiffer Arteries in Young Children

Abstract: Excess early postnatal weight gain leads to vascular changes already in early childhood, characterized by thicker arterial walls. In children who are relatively thin at birth, excess early postnatal weight gain also leads to stiffer arteries. This supports the view that cardiovascular disease risk is associated with growth pattern early in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…The present data indicate that, after spontaneous catch‐up growth towards a normal length and weight, IMT remains augmented in SGA children aged 3–6 years. Previous data have indicated that more weight gain in early infancy leads to a thicker intima‐ media by late childhood and the present data suggest that weight gain in early childhood (age 3–6 years) has comparable effects, perhaps even into young adulthood .…”
Section: Discussionsupporting
confidence: 74%
“…The present data indicate that, after spontaneous catch‐up growth towards a normal length and weight, IMT remains augmented in SGA children aged 3–6 years. Previous data have indicated that more weight gain in early infancy leads to a thicker intima‐ media by late childhood and the present data suggest that weight gain in early childhood (age 3–6 years) has comparable effects, perhaps even into young adulthood .…”
Section: Discussionsupporting
confidence: 74%
“…In this context, birthweight was initially considered a marker of developmental exposure that may relate to later cardio‐metabolic risk. More recently, however, emphasis has turned to rapid early‐life weight gain . Indeed, Leunissen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Current research supports consistent associations of maternal weight gain during gestation, large for gestational age birth size, and rapid weight gain during infancy with BMI, adiposity, or risk of overweight/obesity in childhood through adulthood [46]. Consequences of rapid weight gain in infancy are also linked to adverse cardiovascular and metabolic outcomes later in life [710]. At present, efforts to prevent and treat obesity during childhood have mixed success [11, 12].…”
Section: Introductionmentioning
confidence: 86%